EX OFFICIO AUTHORITY OF JUDGES IN DIVORCE SUIT DECISIONS: AN ANALYIS OF ARTICLE 41 OF LAW NUMBER 1 OF 1974 ON MARRIAGE IN THE PAMEKASAN RELIGIOUS COURT - Khairul Anam; Jamiliya Susantin (Universitas Nurul Jadid, 2026)
The protection of women’s and children’s financial rights after divorce remains a significant issue within the Indonesian Religious Court system. Article 41 of Law Number 1 of 1974 on Marriage normatively obliges the father to bear responsibility for the maintenance and education of children and provides a legal basis for financial obligations toward a former wife. However, in judicial practice, divorce litigation (cerai gugat) decisions often do not consistently stipulate iddah maintenance, mut’ah, and child support within the operative part of the judgment. This inconsistency indicates a gap between the normative construction of Article 41 and its practical implementation in court decisions. This study aims to analyze the obligation of judges’ ex officio authority in divorce litigation decisions and evaluate its implementation at the Religious Court of Pamekasan. The research employs a normative–empirical legal approach through statutory analysis and case study examination of three final and binding divorce judgments issued by the Religious Court of Pamekasan. The findings reveal that variations in the application of ex officio authority are influenced by interpretations of the ultra petita principle, evidentiary considerations, and judicial sensitivity toward the protection of women and children. Drawing on vulnerability theory, this study argues that ex officio authority should be interpreted not merely as judicial discretion but as a juridical obligation inherent in the judicial function. This research contributes to strengthening the doctrinal understanding of judges’ ex officio authority as a mechanism to ensure substantive justice and improve legal protection for women and children after divorce.application of this authority is therefore essential to strengthen legal protection for women and children after divorce.